Elementos de álgebra que auxiliam nos fundamentos do cálculo - Freitas, Iron Felisberto de (2015)
This paper addresses the formal-logical construction of number systems from the set of natural numbers to the real numbers. Being the rst of these sets presented by the axioms of Peano (1858 - 1932) and the latter results of Dedekind cuts (1831 - 1916) on the set of rational numbers. The passage the set of natural numbers to the integers and for these the rational is done by equivalence classes. From a historical perspective, in order to do that mathematics could advance, had to migrate from a sense of \reality" to an abstract concept of number not subject to the amount of idea. Since the beginning of this formal-logical construction of number systems it is necessary to use the concept of correspondences between any two non-empty sets. Finally , are also addressed the polynomial functions of 1st and 2nd degrees and the respective charts in orthogonal Cartesian plane.